Unsplinted Metal Reinforced Implant Retained Overdenture for An Edentulous Arch/ Nur Hafizah Kamar Affendi and Nor Faharina Abd Hamid - Kamar Affendi, Nur Hafizah; Abd Hamid, Nor Faharina (Faculty of Dentistry, 2017)
Objective: This article discuss a clinical case of implant retained overdenture as a predictable and effective treatment for completely edentulous arch. Material and method: A patient with an edentulous maxilla and periodontically compromised teeth in the mandible was treated using a specific surgical and prosthodontic protocol. Patient was followed for 12 months postloading. Result: The implants are still osseointegrated and able to maintain healthy mucosa surrounding implants. The patient have verbally indicated that she is satisfied with the design that gives her comfort and function. Conclusions: It appears that unsplinted freestanding implants can be used as a predictable treatment for edentulous arch.